The effects of musical feedback training on metacognition and self-directed learning - Li, Wen; Manoharan, Pravina; Cui, Xuerong; Liu, Fen; Liu, Ke; Dai, Lu (Frontiers in Human Neuroscience, 2023)
Metacognition and self-directed learning in educational research are recognized for their potential to boost learning efficiency and problem-solving. The present study investigated the impacts of musical feedback training on these competencies among a sample of 84 preservice teachers, aged 18 to 21. The participants were then randomly assigned to experimental or control groups. The results indicate that the training effectively enhanced metacognition, but its impact on self-directed learning readiness was not clear. Significant interaction effect between the experimental and control groups in both metacognition and self-directed learning readiness. Additionally, a positive correlation was identified between metacognition and self-directed learning. The study contributes to the educational discourse by providing empirical evidence on the utility of musical feedback training in fostering metacognition, and by suggesting the need for consistent and long-term engagement in self-directed learning practices. The significance of these findings lies in advocating for the incorporation of music feedback training into music educational curricula, aimed at enhancing metacognition, and thus improving overall learning efficiency.